Standard slot waveguide and double hybrid plasmonic waveguide configurations for enhanced evanescent field absorption methane gas sensing - Butt, Muhammad Ali; Piramidowicz, Ryszard (Photonics Letters of Poland, 2022)
Herein, a numerical study on standard slot waveguide and double hybrid plasmonic waveguide based on a silicon-on-insulator platform is presented. The geometric parameters of both the waveguides are optimized for the operational wavelength of 3.39 μm (absorption line of methane gas) to obtain the maximum evanescent field ratio (EFR). By utilizing Lambert-Beer’s law, the gas sensing capability of both the waveguides is determined. It is found out that both the waveguides of length 100 μm offer high EFR resulting in the 3dB decay of the propagating mode power for the methane gas concentration of 20-22 % in the chamber. The study provides the foundation for the practical realization of compact and highly sensitive gas sensors. Full Text: PDF References J.Y. Yo, Y.S. Kwon, J.W. Lee, J.S. Park, B.H. Rho, W. II. Choi. "Acute Respiratory Distress Due to Methane Inhalation", Tuberculosis and Respiratory Diseases 74, 120-123 (2013). CrossRef M. A. Butt, S. A. Degtyarev, S. N. Khonina and N. L. Kazanskiy. "An evanescent field absorption gas sensor at mid-IR 3.39 μm wavelength", Journal of Modern Optics 64, 1892-1897 (2017). CrossRef M. A. Butt, S. N. Khonina and N. L. Kazanskiy. "Modelling of Rib channel waveguides based on silicon-on-sapphire at 4.67 μm wavelength for evanescent field gas absorption sensor", Optik 168, 692-697, (2018). CrossRef M. A. Butt, S. N. Khonina and S. N. Kazanskiy. "Silicon on silicon dioxide slot waveguide evanescent field gas absorption sensor", Journal of Modern Optics 65, 174-178, (2017). CrossRef S. N. Khonina, N. L. Kazanskiy and M. A. Butt. "Evanescent Field Ratio Enhancement of a Modified Ridge Waveguide Structure for Methane Gas Sensing Application", IEEE Sensors Journal 20, 8469-8476 (2020). CrossRef M.Vlk, A. Datta, S. Alberti, H.D. Yallew, V. Mittal, G. S. Murugan, J. Jagerska. "Extraordinary evanescent field confinement waveguide sensor for mid-infrared trace gas spectroscopy", Light: Science & Applications 10, 26 (2021). CrossRef M.A. Butt, S.N. Khonina, N.L. Kazankiy. "Enhancement of evanescent field ratio in a silicon strip waveguide by incorporating a thin metal film", Laser Physics 29, 076202 (2019). CrossRef M. A. Butt, N. L. Kazanskiy and S. N. Khonina, "Highly integrated plasmonic sensor design for the simultaneous detection of multiple analytes", Current Applied Physics 20, 1274-1280 (2020). CrossRef T. Milde, M. Hoppe, H. Tatenguem, C. Assmann, W. Schade, J. Sacher. "Comparison of the spectral excitation behavior of methane according to InP, GaSb, IC, and QC lasers as excitation source by sensor applications", Applied Optics 58, C84 (2019). CrossRef N. L. Kazanskiy, S.N. Khonina, M.A. Butt. "Polarization-Insensitive Hybrid Plasmonic Waveguide Design for Evanescent Field Absorption Gas Sensor", Photonic Sensors 11, 279-290 (2021). CrossRef D. Popa, F. Udrea. "Towards Integrated Mid-Infrared Gas Sensors", Sensors 19, 2076 (2019). CrossRef S-W. Kang, K. Sasaki, H. Minamitani. "Sensitivity analysis of a thin-film optical waveguide biochemical sensor using evanescent field absorption", Applied Optics 32, 3544-3549 (1993). CrossRef